Penerapan Metode Regresi Linier Untuk Prediksi Jumlah Orang Terlantar Di Provinsi Riau - Windy Amelia Putri; M. Afdal; Permana, Inggih; Zarnelly (Jurnal Sistem Cerdas, 2023)
Displaced people are residents who for some reason cannot meet their needs naturally, both spiritually, physically, and socially. The problem of displaced people occurs for various reasons and urbanization is one of them. Social Service is a government agency that plays a role in improving the quality of social welfare of individuals, groups, and communities. Many community services are carried out by Social Service and one of them is the repatriation of displaced persons. Based on data from the Riau Province Social Service, the number of displaced people in Riau Province from year to year has increased or decreased erratically. This is of course a problem that hinders the Riau Province Social Service in its internal processes such as determining strategies or policies to make decisions. Therefore, this research was conducted to overcome these problems. This research was conducted using the linear regression method with a MAPE result of 7.09% which will be implemented into a prediction application for the number of displaced people and aims to help the Riau Province Social Service get information on the number of displaced people in the next period. Based on the results of the Blackbox test, shows that all menus and features have run very well and obtained a User Acceptance Test (UAT) calculation value of 92%.